A Study of Digital Signature and Its Legal Implications in Context of Bangladesh - Murad, Mohammad Hasan (IIUC Studies, 2012)
The exponential growth of Information and Communication Technology particularly internet has brought about a revolution in the way we do financial and commercial transaction. Electronic commerce opened the door to reach out to global markets. Business has transcended geographical or time limit. More and more, Governments, businesses and consumers are taking advantage of the fast and efficient ways of information technology to conduct commerce. The internet is being used to exchange information; products and services are being designed and marketed ,bought ,sold and even delivered to places which was unimaginable even two decades ago. The internet has helped to achieve true globalization. E-commerce enhances convenience and choice, promote competition, and above all, generate new business opportunities and market efficiencies. However , the growth of e commerce posed a profound concern of security and authenticity of the transactions as internet is open to all and perpetrators are always out there. This concern called for security, authentication and identification measures on internet to prevent fraud and malicious transaction. The technology has responded to this concern by developing online authentication and identification technology namely electronic signature, principally, digital signature. In this paper I have explored the meaning, technology of digital signature and discussed legal issues of digital signature particularly in context of Bangladesh. DOI: http://dx.doi.org/10.3329/iiucs.v6i0.12252 IIUC Studies Vol.6 2010: 111-122